Quantum-Spectroscopic, NCI Analysis and Anticancer Studies of E and Z Conformers of Rhodocorane - Chand, Jinigi Prem; Annapurna, Nowduri; Babu, Bonige Kishore; Manmadarao, Chandaka (Asian Journal of Chemistry, 2025)
In this work, theoretical methods were used to study the optimal geometries, vibrational frequencies and assignments for rhodocoranes E and Z (I & J) conformers. Time-dependent density functional theory (TD-DFT) revealed oscillator strengths and energy values aligning closely with the experiment results. Gauge-independent atomic orbital (GIAO) calculations provided 1H and 13C NMR chemical shifts, compared with the experimental data. The HOMO-LUMO analysis explored charge transfer, while natural bond orbital (NBO) analysis assessed stability via hyper-conjugation and charge delocalization. The molecular electrostatic potential (MEP) surfaces, infrared intensities and topological analyses using electron localization function (ELF) were also performed. Molecular docking studies evaluated anticancer activity against VEGFR-2 kinase inhibitors, targeting protein structures (1Y6B, 4AG8, 6GQO and 6GQP).